Exploiting Metabolic Defects in Glioma with Nanoparticle-Encapsulated NAMPT Inhibitors - Murray, Matthew A.; Noronha, Katelyn J.; Wang, Yazhe; Friedman, Anna P.; Paradkar, Sateja; Suh, Hee-Won; Sundaram, Ranjini K.; Brenner, Charles; Saltzman, W.M.; Bindra, Ranjit S. (Molecular cancer therapeutics, 2024)
The treatment of primary central nervous system tumors is challenging due to the blood–brain barrier and complex mutational profiles, which is associated with low survival rates. However, recent studies have identified common mutations in gliomas [isocitrate dehydrogenase (IDH)-wild-type and mutant, WHO grades II–IV; with grade IV tumors referred to as glioblastomas (GBM)]. These mutations drive epigenetic changes, leading to promoter methylation at the nicotinic acid phosphoribosyl transferase (NAPRT) gene locus, which encodes an enzyme involved in generating NAD+. Importantly, NAPRT silencing introduces a therapeutic vulnerability to inhibitors targeting another NAD+ biogenesis enzyme, nicotinamide phosphoribosyl transferase (NAMPT), rationalizing a treatment for these malignancies. Multiple systemically administered NAMPT inhibitors (NAMPTi) have been developed and tested in clinical trials, but dose-limiting toxicities—including bone marrow suppression and retinal toxicity—have limited their efficacy. Here, we report a novel approach for the treatment of NAPRT-silenced GBMs using nanoparticle (NP)-encapsulated NAMPTis administered by convection-enhanced delivery (CED). We demonstrate that GMX1778 (a NAMPTi) can be formulated in degradable polymer NPs with retention of potency for NAMPT inhibition and anticancer activity in vitro, plus sustained drug release in vitro and in vivo. Direct injection of these drugs via CED into the brain is associated with reduced retinal toxicity compared with systemic administration. Finally, we show that CED of NP-encapsulated GMX1778 to NAPRT-silenced intracranial GBM xenografts in mice exhibit significant tumor growth delay and extends survival. These data support an approach to treat gliomas harboring defects in NAD+ metabolism using CED of NP-encapsulated NAMPTis to greatly improve the therapeutic index and treatment efficacy for this class of drugs.